Island Tongue Flap* - S. Bhattacharya; A. Chaturvedi; M. S. D. Jaiswal; S. K. Bhatnagar; N. C. Misra (Indian Journal of Plastic Surgery)
In a clinico-anatomical study in ten cadavers and 24 patients of oral cancer a new island myomucosal flap, the “Island Tongue Flap” was designed and standardized in our unit. Based on the ipsilateral lingual artery and its venae comitantes this island flap was used to cover defects in the check, floor of mouth and aropharynx. Speech, swallowing and disposal of saliva were least affected post-operatively.